Treatment planning of intensity modulated composite particle therapy with dose and linear energy transfer optimization. (26th May 2017) - Inaniwa, Taku; Kanematsu, Nobuyuki; Noda, Koji; Kamada, Tadashi
Abstract: The biological effect of charged-particle beams depends on both dose and particle spectrum. As one of the physical quantities describing the particle spectrum of charged-particle beams, we considered the linear energy transfer (LET) throughout this study. We investigated a new therapeutic technique using two or more ion species in one treatment session, which we call an intensity modulated composite particle therapy (IMPACT), for optimizing the physical dose and dose-averaged LET distributions in a patient as its proof of principle. Protons and helium, carbon, and oxygen ions were considered as ion species for IMPACT. For three cubic targets of 4  ×  4  ×  4, 8  ×  8  ×  8, and 12  ×  12  ×  12 cm 3, defined at the center of the water phantom of 20  ×  20  ×  20 cm 3, we made IMPACT plans of two composite fields with opposing and orthogonal geometries. The prescribed dose to the target was fixed at 1 Gy, while the prescribed LET to the target was varied from 1 keV µ m −1 to 120 keV µ m −1 to investigate the range of LET valid for prescription. The minimum and maximum prescribed LETs, ( L T_min, L T_max ), by the opposing-field geometry, were (3 keV µ m −1, 115 keV µ m −1 ), (2 keV µ m −1, 84 keV µ m −1 ), and (2 keV µ m −1, 66 keV µ m −1 ), while those by the orthogonal-field geometry were (8 keV µ m −1, 98 keV µ m −1 ), (7 keV µ m −1, 72 keV µ m −1 ), and (8 keV µ m −1, 57 keV µ m −1 ) for the three targets, respectively. To show the proof of principle of IMPACT in a clinical situation, we made IMPACT plans for a prostate case. In accordance with the prescriptions, the LETs in prostate, planning target volume (PTV), and rectum could be adjusted at 80 keV µ m −1, at 50 keV µ m −1, and below 30 keV µ m −1, respectively, while keeping the dose to the PTV at 2 Gy uniformly. IMPACT enables the optimization of the dose and the LET distributions in a patient, which will maximize the potential of charged-particle therapy by expanding the therapeutic window. Further studies and developments will enable this therapeutic technique to be used in clinical practice.